Progressive Overgrowth of the Cerebriform Connective Tissue Nevus in Patients with Proteus Syndrome - Beachkofsky, Thomas M. (2010)
BACKGROUND: Proteus syndrome is a rare overgrowth disorder that almost always affects the skin. OBJECTIVE: Our purpose was to evaluate progression of skin lesions in patients with Proteus syndrome. METHODS: Skin findings were documented in 36 patients with Proteus syndrome. Progression of skin lesions in 16 of these patients was assessed by comparing photographs obtained on repeat visits for an average total duration of 53 months. RESULTS: The skin lesion most characteristic of Proteus syndrome, the cerebriform connective tissue nevus showed progression in 13 children but not in 3 adults. The cerebriform connective tissue nevus progressed by expansion into previously uninvolved skin, increased thickness, and development of new lesions. Lipomas increased in size and/or number in 8/10 children with lipomas. In contrast, epidermal nevi and vascular malformations generally did not spread or increase in number. LIMITATIONS: Only 3 adults with Proteus syndrome were evaluated longitudinally. CONCLUSION: The cerebriform connective tissue nevus in Proteus syndrome grows throughout childhood but tends to remain stable in adulthood.